Synthesis and characterization of aromatic copolyesters containing siloxane linkages in the polymer backbone - Waghmare, P. B.; Idage, Susheela B.; Menon, Shamal K.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A new series of aromatic copolyesters containing siloxane linkages were prepared by the melt polymerization of bisphenol A (BPA) with eugenol end-capped siloxane (EuSi), diphenyl terephthalate (DPT), and diphenyl isoplithalate (DPI) in varying ratio in the temperature range 220-290 degrees C under reduced pressure in the presence of dibutyl tin dilaurate (DBTL) catalyst. The siloxane copolyesters prepared were characterized by FTIR, H-1-NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of eugenol end-capped siloxane was studied on the properties of BPA/DPI/DPT copolyesters. The glass-transition temperature of copolyester was decreased from 184 to 70 degrees C by incorporation of 20% of eugenol endcapped siloxane. All copolyesters were found to be soluble in commonly used aprotic polar solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: aromatic copolyesters; Bisphenol A; diphenyl isophthalate; diphenyl terephthalate; eugenol end-capped siloxane; melt polymerization

Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Electrochemical fluorescence switching from a patternable poly(1,3,4-oxadiazole) thin film - Seo, Seogjae; Kim, Yuna; You, Jungmok; Sarwade, Bhimrao D.; Wadgaonkar, Prakash P.; Menon, Shamal K.; More, Arvind S.; Kim, Eunkyoung (Macromolecular Rapid Communications, 2011)
A highly soluble poly(1,3,4-oxadiazole) (POD) substituted with long alkyl chains was examined for electrochemical fluorescence switching. The high solubility of the polymers enabled a simple fabrication of an electrochemical cell, which showed reversible fluorescence switching between dark (n-doping) and bright (neutral) states with a maximum on/off ratio of 2.5 and a cyclability longer than 1000 cycles. Photochemical cleavage of the oxadiazole in POD allowed photo-patterning of the POD film upon exposure to UV source. The patterned POD films displayed patterned image reversibly under a step potential of +1.8/-1.8V.
Keywords: fluorescence; lithography; Luminescence; photochemistry; switching device

Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP

New poly(1,3,4-oxadiazole)s bearing pentadecyl side chains: synthesis and characterization - More, Arvind S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2012)
The 4-[4'-(Hydrazinocarbonyl)phenoxy]-2-pentadecylbenzohydrazide was polycondensed with aromatic diacid chlorides viz., terephthalic acid chloride (TPC), isophthalic acid chloride (IPC), and a mixture of TPC : IPC (50 : 50 mol %) to obtain polyhydrazides which on subsequent cyclodehydration reaction in the presence of phosphoryl chloride yielded new poly(1,3,4-oxadiazole)s bearing flexibilizing ether linkages and pentadecyl side chains. Inherent viscosities of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 0.530.66 dL g(-1) and 0.490.53 dL g(-1), respectively, indicating formation of medium to reasonably high molecular weight polymers. The number average molecular weights (M-n) and polydispersities (M-w/M-n) of poly(1,3,4-oxadiazole)s were in the range 14,660-21,370 and 2.22.5, respectively. Polyhydrazides and poly(1,3,4-oxadiazole)s were soluble in polar aprotic solvents such as N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, and N,N-dimethylformamide. Furthermore, poly(1,3,4-oxadiazole)s were also found to be soluble in solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, and m-cresol. Transparent, flexible, and tough films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from N,N-dimethylacetamide and chloroform solutions, respectively. Both polyhydrazides and poly(1,3,4-oxadiazole)s were amorphous in nature and formation of layered structure was observed due to packing of pentadecyl chains. A decrease in glass transition temperature was observed both in polyhydrazides (143-166 degrees C) and poly(1,3,4-oxadiazole)s (90-102 degrees C) which could be ascribed to internal plasticization effect of pentadecyl chains. The T-10 values, obtained from TG curves, for poly(1,3,4-oxadiazole)s were in the range of 433-449 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 124:1281-1289, 2012
Keywords: 3; 4-oxadiazole)s; Cashew nut shell liquid; pentadecyl; poly(1; polyhydrazides; thermal stability

Sustainable polyacetals from isohexides - Rajput, B. S.; Gaikwad, S. R.; Menon, Shamal K.; Chikkali, Samir H. (Green Chemistry, 2014)
A single step synthetic protocol to access a small family of renewable diacetals was established. The resultant chiral diacetals are valuable building blocks in pharmaceuticals and materials science. To demonstrate their synthetic competence, isohexide-diacetals (2a-c) were subjected to acetal metathesis polymerization and the corresponding polymers (poly2a-c) were isolated as white solids with molecular weights in the range 3200-27 600 (g mol(-1)). The semi-crystalline polymers displayed glass transition temperatures between 38-65 degrees C and melting temperatures in the range 103-156 degrees C. The isohexide derived polyacetats are stable under practical washing and rinsing conditions but degrade in slightly acidic media.

New atom transfer radical polymerization initiator based on phenolphthalein for the synthesis of bis-allyloxy functionalized polystyrene macromonomers - Patil, Sachin S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Polymer International, 2015)
A new atom transfer radical polymerization (ATRP) initiator, namely 2-(1,1-bis(4-(allyloxy)phenyl)-3-oxoisoindolin-2-yl)ethyl 2-bromo-2-methylpropanoate, was synthesized starting from phenolphthalein, a commercially available and an inexpensive chemical. Well- defined bis-allyloxy functionalized polystyrene macromonomers (M-n,M-GPC 4800-11 700gmol(-1)) with controlled molecular weight and narrow molecular weight distribution (1.05-1.09) were synthesized using ATRP by varying the monomer to initiator feed ratio. The presence of allyloxy functionality on polystyrene was confirmed by Fourier transform infrared and H-1 NMR spectroscopy. A kinetic study of polymerization revealed pseudo-first-order kinetics with respect to monomer consumption. Initiator efficiency was found to be in the range 0.80-0.95. Matrix-assisted laser desorption ionization time of flight spectra showed a narrow molecular weight distribution with control over the molecular weight. The reactivity of the allyloxy groups on polystyrene was successfully demonstrated by quantitative photochemical thiol-ene click reaction with benzyl mercaptan as the model thiol reagent. Furthermore, the thiol-ene click reaction was exploited to introduce other reactive functional groups such as hydroxyl and carboxyl by reaction of ,-bis-allyloxy functionalized polystyrene with 2-mercaptoethanol and 3-mercaptopropionic acid, respectively. (c) 2014 Society of Chemical Industry
Keywords: atom transfer radical polymerization; bis-allyloxy functionalized polystyrene; functional initiator; phenolphthalein; thiol-ene click reaction

Synthesis of renewable copolyacetals with tunable degradation - Rajput, Bhausaheb S.; Chander, Umesh; Arole, Kailash; Stempfle, Florian; Menon, Shamal K.; Mecking, Stefan; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2016)
Acetal metathesis copolymerization (AMCP) of renewable isohexide diacetals and aliphatic long-chain diacetals is reported and access to a small family of copolyacetals has been established. Crucial 1-2D NMR and MALDI-ToF-MS findings unambiguously confirm the existence of a copolymeric structure. In a stark contrast to the earlier reported isohexide-polyacetals, the current copolyacetals reveal very slow degradation. Hydrolytic degradation of copolyacetal pellets is extremely slow at pH 7, whereas only 30% degradation over a period of 15 d is observed in 9 M hydrochloric acid solution. GPC investigations reveal that with increasing chain-length the rate of degradation reduces, whereas copolyacetals with short-chain aliphatic segments display a faster degradation profile. The reduced rate of degradation can be attributed to the hydrophobic nature of long-chain acetal segments. In situ NMR spectroscopy reveals the existence of formates, hemiacetals, and diols as degradation products. Thus, the rate of degradation can be tuned by the judicious choice of isohexide-diacetal and linear-diacetals in a copolyacetal.
Keywords: copolyacetals; degradable polymers; diacetals; isohexides; renewable polymers

Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers

Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.